2013
DOI: 10.1159/000345130
|View full text |Cite
|
Sign up to set email alerts
|

Asthmatic Response to Milk Ingestion Challenge in Adults: A Comparison of the Open and Double-Blind Challenges

Abstract: Background: Cow’s milk allergy can participate in pathophysiological mechanisms underlying bronchial asthma in some adult patients. This role should ultimately be confirmed by means of a milk ingestion challenge. In this study, the diagnostic value of the open food ingestion challenge (OFICH) and the double-blind placebo-controlled food challenge (DBPCFC) techniques with milk were compared in adult patients suffering from bronchial asthma with suspected milk allergy. Methods: In 87 asthmatics with a suspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The five types of asthmatic response induced by food ingestion challenge in bronchial asthma patients, described in this as well as in our previous papers [7,19,[23][24][25]84], may be comparable with the basic types of the asthmatic response to the bronchial challenge with inhalant allergens [76][77][78][79].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The five types of asthmatic response induced by food ingestion challenge in bronchial asthma patients, described in this as well as in our previous papers [7,19,[23][24][25]84], may be comparable with the basic types of the asthmatic response to the bronchial challenge with inhalant allergens [76][77][78][79].…”
Section: Discussionsupporting
confidence: 69%
“…Some investigators suggested a possible participation of immune-complexes, whereas others presumed involvement of IgE antibodies and/or various modifications of the IgEmediated hypersensitivity mechanisms. In the DYAR to food ingestion challenge, described already by usin the past [7,19,23,84], which is analogical to the DYAR induced by inhalant allergens [78,79] the involvement of the cell-mediated hypersensitivity mechanism(s) could be presumed. Nevertheless, there is still a great dearth of structural information and research data concerning the exact role and the mode of involvement of immunological mechanisms in the particular types of the food-induced asthmatic response in large group of well-defined and diagnosed patients with bronchial asthma.…”
Section: Discussionmentioning
confidence: 97%
“…Food allergy should be investigated in the case of rapid onset, unexpected asthma attacks related to food exposure ( 56 ). Anyway, exacerbations can occur not only immediately after food intake but also, rarely, in the late phase, even after 24 h ( 65 ). Furthermore, it should be taken into account that additives ( 66 , 67 ) may trigger bronchospasm, too.…”
Section: Managementmentioning
confidence: 99%
“…Nguyen also reported not having observed any acute or delayed deterioration of pulmonary functions among 25 atopic asthmatic adults exposed to cow's milk versus placebo [32]. Of note, asthmatic patients with known milk allergy [33]. Nevertheless, our study excluded children with present known allergy to cow's milk.…”
Section: Discussionmentioning
confidence: 76%
“…Of note, asthmatic patients with known milk allergy act differently. Eighty-six percent of asthmatic adults with bronchial asthma and p ositive skin tests for milk developed a positive asthmatic response to milk challenge measured by spirometry [ 33 ]. Nevertheless, our study excluded children with present known allergy to cow’s milk.…”
Section: Discussionmentioning
confidence: 99%